ASSOCIATION BETWEEN NONSUICIDAL SELF-INJURY AND DEPRESSION, ANXIETY, AND STRESS AMONG STUDENTS AT TAN PHU HIGH SCHOOL, DONG NAI PROVINCE, VIETNAM (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of nonsuicidal self-injury, depression, anxiety, and stress and examine their associations among students at Tan Phu High School, Dong Nai province in 2025.Subjects and methods: A cross-sectional study was conducted among 996 students at Tan Phu High School from September 2024 to April 2025. Data were collected using a self-administered questionnaire including demographic information, the DASS-21, and the FASM.Results: The prevalence of nonsuicidal self-injury was 34.4%. The prevalence of depression, anxiety, and stress was 50.2%, 59.5%, and 50.8%, respectively. Students with depression, anxiety, and stress were 1.66, 1.69, and 1.53 times more likely to engage in nonsuicidal self-injury compared with those without these conditions.Conclusions: Nonsuicidal self-injury among students at Tan Phu High School was relatively common and was significantly associated with depression, anxiety, and stress. Early detection and psychological support interventions in schools are needed.
Keywords: Self-injury, depression, anxiety, stress, high school students.